Pilot Study Waqf Pesantren Gontor and Poverty Reduction: A Study by Using Smart PLS-SEM Approach - Andi Triyawan (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
This paper aims to examine waqf Pesantren Gontor affecting the poverty alleviation in Indonesia. The pilot project is based on a sample of 30 responsible In several business units in Pesantren Gontor such as Gontor’s Taylor unit, Gontor’s Supermarket, Gontor’s Bakery and Gontor’s food court. The study used partial least squares structural equation modelling tool to analyze data which provide evidence of realibility and validity. The empirical results show that Waqf business units (source of fund, profitability, Business Capital, Product Innovation, market need) are significantly positive affected with Human Resources Development and Waqf Pesantren Gontor. Moreover, Waqf Pesantren Gontor are significantly positive affected with poverty alleviation. The finding of the study will be a bench mark or the board for policy makers and implementers in torching the avenue of Waqf Pesantren improvement and Poverty alleviation.